Landscape analysis and overview of the literature on oxidative stress and pulmonary diseases - Liu, Xin; Wang, Xiaofan; Chang, Jing; Zhang, Hongmin; Cao, Pengxiu (Frontiers in Pharmacology, 2023)
Oxidative stress is caused by an imbalance in oxidant/antioxidant processes and is a critical process in pulmonary diseases. As no truly effective therapies exist for lung cancer, lung fibrosis and chronic obstructive pulmonary disease (COPD), at present, it is important to comprehensively study the relationship between oxidative stress and pulmonary diseases to identify truly effective therapeutics. Since there is no quantitative and qualitative bibliometric analysis of the literature in this area, this review provides an in-depth analysis of publications related to oxidative stress and pulmonary diseases over four periods, including from 1953 to 2007, 2008 to 2012, 2013 to 2017 and 2018 to 2022. Interest in many pulmonary diseases has increased, and the mechanisms and therapeutic drugs for pulmonary diseases have been well analyzed. Lung injury, lung cancer, asthma, COPD and pneumonia are the 5 most studied pulmonary diseases related to oxidative stress. Inflammation, apoptosis, nuclear factor erythroid 2 like 2 (NRF2), mitochondria, and nuclear factor-κB (NF-κB) are rapidly becoming the most commonly used top keywords. The top thirty medicines most studied for treating different pulmonary diseases were summarized. Antioxidants, especially those targeting reactive oxygen species (ROS) in specific organelles and certain diseases, may be a substantial and necessary choice in combined therapies rather than acting as a single "magic bullet" for the effective treatment of refractory pulmonary diseases.